Low temperature synthesis of MgTa2O6 powders - Navale, SC; Samuel, V; Ravi, V (Materials Letters, 2005)
A combination of digestion and further low temperature calcination to crystallize the product is employed to prepare MgTa2O6 (MT) ceramics. Freshly prepared niobium hydroxide gel is mixed with magnesium hydroxide thoroughly and allowed to react at 100 degrees C under refluxing and stirring conditions for 6-12 h. The X-ray amorphous product so formed is heated at 550 degrees C to form crystalline MgTa2O6. This is the lowest temperature so far reported for the formation of MgTa2O6. For comparison, MT powders were also prepared by the traditional solid state method. Transmission electron microscope (TEM) investigations revealed that the average particle size is 40 nm for the low temperature calcined powders. (C) 2005 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Electron microscopy; magnesium tantalate; Oxides; X-ray diffraction